MATH SOLVE

9 months ago

Q:
# 1. What values of a, b, and c would you use in the quadratic formula for the following equation?5x^2 + 9x = 4a. a= -4, b = 9, c = 5b. a = 5, b = 9, c = -4c. a = 5, b = -4, c = 9d. a = 5, b = 9, c = 4 (I think it might be this one)2. Which expression gives the solutions of -5 + 2x^2 = -6x ?( see attachment)3. Which method is the best method for solving the equation 8x^2 - 13x + 3 = 0?a. square rootsb. factoringc. graphingd. quadratic formulaEven if you can only answer one of these please still answer, thank you!

Accepted Solution

A:

Question (1):

The general formula of the quadratic equation is:

ax² + bx + c = 0

The given equation is:

5x² + 9x = 4

Rearrange the given equation to look the standard one:

5x² + 9x - 4 = 0

Now, compare the coefficients in the given equation with the standard one, you will find that:

a = 5, b = 9 and c = -4

Question (2):

The given expression is:

-5 + 2x² = -6x

Rearrange this expression to be in standard form:

2x² + 6x - 5 = 0

This means that:

a = 2

b = 6

c = -5

The roots of the equation can be found using the formula in the attached image.

Substituting in this formula with the given a, b and c, we would find that the correct choice is third one (I have attached the correct choice)

Question (3):

Quadratic formula (the one used in the previous question, also shown in attached images) is the best method to get the solution of any quadratic equation. This is because, putting the equation in standard form, we can simply get the values of a, b and c, substitute in the formula and get the precise solutions of the equation.

Hope this helps :)

The general formula of the quadratic equation is:

ax² + bx + c = 0

The given equation is:

5x² + 9x = 4

Rearrange the given equation to look the standard one:

5x² + 9x - 4 = 0

Now, compare the coefficients in the given equation with the standard one, you will find that:

a = 5, b = 9 and c = -4

Question (2):

The given expression is:

-5 + 2x² = -6x

Rearrange this expression to be in standard form:

2x² + 6x - 5 = 0

This means that:

a = 2

b = 6

c = -5

The roots of the equation can be found using the formula in the attached image.

Substituting in this formula with the given a, b and c, we would find that the correct choice is third one (I have attached the correct choice)

Question (3):

Quadratic formula (the one used in the previous question, also shown in attached images) is the best method to get the solution of any quadratic equation. This is because, putting the equation in standard form, we can simply get the values of a, b and c, substitute in the formula and get the precise solutions of the equation.

Hope this helps :)